2022
DOI: 10.21203/rs.3.rs-2213546/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinicopathological significance of peritumoral alveolar macrophages in patients with resected early-stage lung squamous cell carcinoma

Abstract: Introduction: This study aimed to clarify the correlation between the number of AMs and prognosis and to examine the gene expression of AMs in lung squamous cell carcinoma (SqCC). Methods: We reviewed 124 stage I lung SqCC cases in our hospital and 139 stage I lung SqCC cases in The Cancer Genome Atlas (TCGA) cohort in this study. We counted the number of AMs in the peritumoral lung field (P-AMs), and in the lung field distant from the tumor (D-AMs). Moreover, we performed a novel ex vivo bronchoalveolar lavag… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…The difference in MLR between squamous and non-squamous NSCLC may be due to differences in cellular immune responses during the carcinogenesis process of the two types of lung cancer. A Japanese study showed an increased number of alveolar macrophages located close to the tumor cell collection (peritumoral) was an independent risk factor of poor prognosis for stage I squamous cell carcinoma lung cancer, illustrating the role of macrophages in the progression of squamous cell carcinoma lung cancer [20].…”
Section: International Journal Of Scientific Advances Issn: 2708-7972mentioning
confidence: 99%
“…The difference in MLR between squamous and non-squamous NSCLC may be due to differences in cellular immune responses during the carcinogenesis process of the two types of lung cancer. A Japanese study showed an increased number of alveolar macrophages located close to the tumor cell collection (peritumoral) was an independent risk factor of poor prognosis for stage I squamous cell carcinoma lung cancer, illustrating the role of macrophages in the progression of squamous cell carcinoma lung cancer [20].…”
Section: International Journal Of Scientific Advances Issn: 2708-7972mentioning
confidence: 99%